Spatial Organization of Traditional Settlement in Toweren Village, Lut Tawar Subdistrict, Aceh Tengah - Rahmah, Meutia; Agustina, Sylvia; Djamaluddin, Masdar; Wulandari, Elysa (Rumoh Journal of Architecture, 2023)
Aceh Tengah Regency, as one of the regions with significant natural and cultural tourism potential in Aceh Province, has experienced various changes in its community settlement patterns. However, these changes have not occurred uniformly across all villages. For example, Toweren Village in Lut Tawar District continues to preserve its traditional houses and local wisdom amid the tide of modernization. The phenomenon of maintaining traditional values amidst contemporary developments is an interesting subject for study, particularly in the context of socio-cultural changes and settlement spatial patterns. This study aims to analyze the spatial pattern of settlements in Toweren Village, which is shaped by the interaction between local culture and the dynamics of changing times. The research method used is descriptive evaluation, employing both primary and secondary surveys for data collection. The analysis is conducted by presenting maps, written sources, and field observations, which are then described. The results show that the macro spatial concept in Toweren Village is formed through the physical arrangement of the settlement environment, reflecting the division of space based on land use. Residential areas are located in the village center, while agricultural and plantation lands lie outside the residential zone. At the micro scale, housing occupancy follows the hulu-teben spatial layout concept, which serves as the basis for regulating the position and function of spaces within the settlement. Areas with higher topography are considered more sacred than those with lower topography. The settlement pattern of Toweren Uken follows a top-down concept, with a hierarchical spatial structure from the center outward, in accordance with cultural values. Initially concentrated around Umah Pitu Ruang, the settlement pattern has now spread throughout the village. Changes are also evident in the increasingly narrow yards of houses due to population growth, illustrating the dynamic between preserving traditional spatial patterns and socio-demographic development.